Experience and challenges on influenza and pertussis vaccination in pregnant women - Shabir A. Madhi; Marta C. Nunes (Human Vaccines & Immunotherapeutics, 2018)
Young infants contribute to relatively high burden of vaccine-preventable diseases, including infections by influenza virus and Bordetella pertussis. Vaccination of pregnant women can enhance transplacental transfer of protective antibody to the fetus and protect the infant against disease during the first few months of life. Pregnant women are a priority group for seasonal influenza vaccination, due to third-trimester pregnancy being a risk-factor for severe influenza illness. Furthermore, randomized controlled trials confirmed that influenza vaccination during pregnancy confers protection against influenza-confirmed illness in the women, and their infants up to 3 months of age; and is also associated with 20% reduction in all-cause pneumonia among young-infants. Maternal influenza vaccination might also reduce the risk of low-birth weight, preterm births, and stillbirths however, data on this is conflicting. Vaccination of pregnant women with acellular pertussis vaccines reduces pertussis in their young infants by up to 93%. The increase in specific pertussis antibody among the infants born to vaccinated women might, however, interfere with the active pertussis vaccination of the infant following the primary series of vaccines. The clinical implication of this is yet to be ascertained, particularly since immune responses following the booster vaccine are unaffected. Vaccination of pregnant women with inactivated influenza vaccine and acellular pertussis vaccine have been demonstrated to confer protection to their young infants, and warrants consideration for inclusion into public health immunization programs, including in low and middle income countries.